Effect of Protein O-Mannosyltransferase (MSMEG_5447) on M. smegmatis and Its Survival in Macrophages - Jia, Liqiu; Sha, Shanshan; Yang, Shufeng; Taj, Ayaz; Ma, Yufang (Frontiers in Microbiology, 2021)
Protein O-mannosyltransferase (PMT) catalyzes initial step of protein O-mannosylation of Mycobacterium tuberculosis (Mtb) and playsa crucial role for Mtb survival in the host. To better understand the role of PMT in the host innate immune response during mycobacterial infection, in this study, we utilized Mycobacterium smegmatis pmt (MSMEG_5447) gene knock out strain, ΔM5447 to infect THP-1 cells. Our results revealed that the lost of MSMEG_5447 not only impaired the growth of M. smegmatis in 7H9 medium but also reduced the resistance of M. smegmatis against lysozyme and acidic stress in vitro. Macrophage infection assay showed that ΔM5447 displayed attenuated growth in macrophages at 24 hours post infection. The production of TNF- and IL-6 and the activation of transcription factor NF-kB were decreased in ΔM5447-infected macrophages, which were further confirmed by transcriptomic analysis. Moreover, ΔM5447 failed to inhibit phagosome-lysosome fusion in macrophages. These findings revealed that PMT played a role in modulating the innate immune response of host, broaden our understanding for functions of protein O-mannosylation in mycobacterium-host interaction.